Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy in Reducing Craving in Women Consuming Crystal Drug - Mohammadi, Maryam; Hassani, Fariba; Emamipour, Suzan; Golshani, Fatemeh (Novelty in Biomedicine, 2020)
Background: The aim of this study was to compare the effectiveness of cognitive-behavioral therapy and acceptance-commitment based therapy in decreasing drug craving in women who were addicted to the crystal. Materials and Methods: The research method was quasi-experimental pre-test-post-test with the control group and two methods; the cognitive-behavioral, and the acceptance and commitment therapy were separately followed for two experimental groups with a follow-up phase. The statistical population of this study was all women who were addicted to the crystal that referred to addiction treatment centers in Isfahan province during the period of August to October 2017. They were simultaneously depressed. The instruments used in the study were the Wilson, Guilford and Concrete protocol (2004) that is the treatment based on the acceptance, Carole's cognitive-behavioral therapy (1998), and Frankl (2002) craving for drug questionnaire, as well as repeated measures of variance analysis. Results: Findings showed that cognitive-behavioral and acceptance and commitment therapies for craving of crystal usage are effective in women who have had crystal abuse. Between two methods of cognitive behavioral therapy, and acceptance and commitment therapy in the field of craving for the crystal in women that overcome drug addiction, there was a significant difference. The acceptance and commitment therapy had effects that are more therapeutic. Conclusion: Therefore, this study provides a total empirical support for acceptance-based and commitment treatment in the treatment of women who were overcoming the crystal addition.